A Novel Strategy for Led Re-Utilization for Visible Light Communications - Soto-Gomez, J; Adasme-Soto, P; Seguel-Gonzalez, F (Elsevier GmbH, 2017)
A resource allocation optimization model for downlink indoor Optical Wireless Communications networks (OWC) is proposed in this paper. The optimization problem is formulated as a mixed integer binary problem. A centralized smart coordinator solves the problem in order to assign efficiently Visible Light Communications (VLC) channels to users. The optimization problem is solved with two different approaches based on Cuckoo Search algorithm (CS). The first one solves the complete network problem considering all users and access points simultaneously with a random initialization procedure. Whilst the second approach is a CS based decomposition procedure, which obtains feasible solutions with the help of a spatial reuse aided algorithm. Both procedures were tested for different receivers Fields of View (FOV), e.g., FOV = 30° and 60° which are placed randomly on the coverage area and for different transmitter s power levels. Results show that the solutions obtained with spatial reuse aided procedure outperforms the first approach in terms of total network throughput for different power levels, i.e., 1 and 10 W, and different number of users. Finally, results obtained with the second approach allow the usage of a wider FOV. © 2017 Elsevier GmbH